Vrednost spornega predmeta pri alternativnem reševanju potrošniških sporov - Čertanec, Ana (Pravnik, 2014)
The proposal of the Act on alternative dispute resolution for consumer disputes proposes minimum and maximum values of the matter in dispute for access to the alternative dispute resolution entity. While, according to the author, the determination of the maximum value of the matter in dispute is not questionable, problems may occur while trying to determine the lowest value of the matter in dispute. Since the consumer is still able to file an application before the court, where restrictions do not apply, determining the minimum value of the matter in dispute in consumer alternative dispute resolution is not inadmissible, since this does not violate the right to judicial protection. Nevertheless, the author of the paper opposes to such limitation and presents arguments in favor of the idea that for the sake of consumer protection and enforcement of its rights, such regulation is not appropriate, because most violations of consumer rights happen just there - in small values of the matter in dispute. The paper also examines the regulation of other European countries in the field of consumer alternative dispute resolution and tries, using a comparative overview, to underline the argument that the proposed Slovenian regulation does not have justified reasons.
Keywords: alternativne oblike; potrošniki; reševanje; spori; trade; trgovina; varstvo potrošnikov; vrednost